Solubility of Polysaccharides 2017
DOI: 10.5772/intechopen.71385
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Chitin: Solvents, Solution Behaviors and Their Related Mechanisms

Abstract: Chitin is a natural polysaccharides having a unique molecular arrangement of 2-(acetylamino)-2-deoxy-d-glucose, it possesses multifunctional properties and is suitable for various applications mainly in pharmaceutical, biomedical food, textiles and packaging fields. Therefore, being considered as a superior material for a sustainable future of industrial development, chitin perfectly meets up the demands with diversified functionalities in applications, excellent biocompatibility and biodegradability. Non-toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
106
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(119 citation statements)
references
References 52 publications
(53 reference statements)
2
106
0
1
Order By: Relevance
“…In recent years, alkaline solvent systems, mainly based on NaOH or KOH, have been proposed for the dissolution of crustacean chitin [18,19], β-glucans [20,21] and cellulose [22,23] from plant sources, and yeast CGC [24]. The addition of urea to the alkali solution was reported to enhance the polymers' solubilization by disrupting the inter-and intramolecular hydrogen bonds [25,26]. Moreover, it was reported that low temperature steps (below freezing point of the solvent system) plays an important role in the solubilization process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, alkaline solvent systems, mainly based on NaOH or KOH, have been proposed for the dissolution of crustacean chitin [18,19], β-glucans [20,21] and cellulose [22,23] from plant sources, and yeast CGC [24]. The addition of urea to the alkali solution was reported to enhance the polymers' solubilization by disrupting the inter-and intramolecular hydrogen bonds [25,26]. Moreover, it was reported that low temperature steps (below freezing point of the solvent system) plays an important role in the solubilization process.…”
Section: Introductionmentioning
confidence: 99%
“…At such low temperatures, the hydrated alkali component disrupts the polymer chain matrix by breaking the hydrogen bonds and allowing the formation of new ones. This yields a stable structure composed of the polymer chain associated with the alkali component and water clusters [25,27]. The solubilization of the polymer chains is allowed by the volume expansion of the matrix upon freezing-induced strength and disruption of the hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The solubility of chitosan in 1% acetic acid solution mainly depends on the DD% value and on the acetyl group distribution along the chains (Roy et al, 2017; Younes & Rinaudo, 2015). Chitin with a DD% above 55% can be solubilized gradually.…”
Section: Resultsmentioning
confidence: 99%
“…With all crude extracted chitin from different fermentation carbon sources having a degree of deacetylation higher than 50% or a degree of acetylation lower than 50%, it is concluded that all obtained crude extracted chitin samples contain chitosan. Chitosan obtained from the partial deacetylation of chitin becomes soluble in aqueous acidic medium once the degree of acetylation falls below 50% (Roy et al 2017). Due to poor solubility of chitin, chitin has more biological applications when partially deacetylated to chitosan and is more easily processed into various biomaterials (Ibrahim and El-Zairy 2015).…”
Section: Discussionmentioning
confidence: 99%